Assessment of Social Competence of Adolescents With Substance-Abusing Parents in High Schools in West of Tehran - Mehrnoush Inanlou; Naiemeh Seyedfatemi; Zahra Abbasi; Shima Haghani (Iran University of Medical Sciences, 2022)
Background & Aims: Substance abuse is a chronic disease that affects the person, in addition to their family and children. Adolescents' social competence is one of the issues that seems to be affected by parental substance abuse. Social competence is the level of commitment to acceptable social behaviors that are needed in society to effectively interact with others. The present study aims to determine the social competence of adolescents with parents having substance abuse in the West of Tehran. Materials & Methods: This is a cross-sectional study that was conducted in 2020. Participants were 265 adolescents in the first and second public high schools in the west of Tehran (districts 5, 10, 18), who had parents with substance abuse. They were selected by a continuous sampling method. After the necessary arrangements and obtaining informed consent from them, the link of the online questionnaires was provided to them through social media applications. The data collection tool included a demographic form and the Perceived Social Competence Scale. To analyze the collected data, descriptive statistics (frequency, percentage, mean, standard deviation) and inferential statistics (independent t-test, one-way analysis of variance) were used in SPSS software v.16, and the significance level was set at 0.05. Results: This is a cross-sectional study that was conducted in 2020. Participants were 265 adolescents in the first and second public high schools in the west of Tehran (districts 5, 10, 18), who had parents with substance abuse. They were selected by a continuous sampling method. After the necessary arrangements and obtaining informed consent from them, the link of the online questionnaires was provided to them through social media applications. The data collection tool included a demographic form and the Perceived Social Competence Scale. To analyze the collected data, descriptive statistics (frequency, percentage, mean, standard deviation) and inferential statistics (independent t-test, one-way analysis of variance) were used in SPSS v.16 software, and the significance level was set at 0.05. Conclusion: Nurses and psychiatrists can identify the affected children in counseling and treatment centers while providing care to the parents suffering from substance abuse. By providing appropriate programs such as life skill education, they can empower children to deal with the problems caused by parental substance abuse and help their growth and future success.